(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Menopause is a natural biological transition, yet in many underserved communities, it is misunderstood as a disease, supernatural affliction, or cause of social isolation. Women face psychological distress, marital struggles, and limited healthcare access, worsening their quality of life. Objectives: This study aims to examine menopause-related stigma, psychological challenges, and healthcare accessibility gaps in low-resource settings. It presents qualitative findings from structured interviews with ten perimenopausal women to identify barriers to medical support, emotional struggles, and cultural misconceptions. Methods: A qualitative research approach was employed, including structured in-depth interviews with ten perimenopausal women from underserved communities. Thematic analysis was conducted to extract key trends regarding healthcare attitudes, social stigma, and psychological effects of menopause. Results: Interviewed women reported, Social stigma and marital distress due to misconceptions about infertility and loss of attractiveness. Severe mood swings, aggression, and depressive symptoms, often misinterpreted as mental instability. Fear of rejection or second marriages, preventing open communication with spouses about menopause symptoms Shame in discussing urinary incontinence and sexual dysfunction, leading to emotional isolation. Conclusion: Findings emphasize the urgent need for structured menopause education, accessible healthcare interventions, and culturally informed counseling services. This research advocates for policy-driven healthcare initiatives, community outreach programs, and inclusive medical training to combat stigma and improve women’s well-being.